The Effect of using the Multimedia Method in Teaching Some of the Basic Skills of Football in the Students of the Second Stage in the Faculty of Physical Education and Sports Sciences - Hussein Habib Mosleh (Journal of Global Pharma Technology, 2016)
The objective of the research is to prepare an educational program using multimedia. Learn about the effect of using the multimedia method in learning some basic skills of football for students of the Faculty of Physical Education and Sports Science. The researcher stressed that there is a clear impact of the educational program using the method of multimedia in learning the basic skills of football students of the Faculty of Physical Education and Sports Science Anbar University. The researcher used the experimental method in the design of the experimental and control groups. The study sample was 60 students divided into two groups of 30 students per group. The duration of the curriculum was from 25/2/2018 to 27/4/2018 at two units per week and six weeks. That there is an impact of this approach in the learning of students in the skills of football. Hence the researcher stressed through the most important recommendations that the program prepared can be applied by the colleges concerned and for different skills and other games.Keywords: Multimedia, Scoring, Handling, Rolling and putting down and football.